2008
DOI: 10.1002/pd.1973
|View full text |Cite
|
Sign up to set email alerts
|

Prader‐Willi syndrome: is there a recognizable fetal phenotype?

Abstract: Objectives To determine fetal features, which could lead to the diagnosis of Prader-Willi syndrome (PWS) during pregnancy. MethodsWe analyze the ultrasound features, genetic studies and pathologic findings in two cases of PWS diagnosed during pregnancy. ResultsIn the first case, diminished fetal movement, polyhydramnios and oddly positioned hands and feet suggested PWS. Methylation studies confirmed diagnosis and a deletion was detected in the 15q11-q13 region. In the second case, similar ultrasound findings l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 14 publications
7
34
0
Order By: Relevance
“…Cytogenetic analysis confirmed the presence of partial monosomy 15 [Le Bris-Quillevere et al, 1990;Surh et al, 1994;Chang et al, 2014] or trisomy 15 in the cultures, both of which are associated with an increased risk of UPD [Surh et al, 1994Christian et al, 1996Roberts et al, 1997;Slater et al, 1997;L'Herminé et al, 2003]. Genetic testing in three other cases was performed because of various combinations of fetal abnormalities found on ultrasound examination (short femur, reduced AC, abnormal posturing of hands, hypogonadism, reduced fetal movements, polyhydramnios, breech presentation and mild hydronephrosis) [Le Bris-Quillevere et al, 1990;Bigi et al, 2008]. In our cohort, 23 amniocenteses were performed and all fetuses had a normal karyotype using Giemsa staining.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Cytogenetic analysis confirmed the presence of partial monosomy 15 [Le Bris-Quillevere et al, 1990;Surh et al, 1994;Chang et al, 2014] or trisomy 15 in the cultures, both of which are associated with an increased risk of UPD [Surh et al, 1994Christian et al, 1996Roberts et al, 1997;Slater et al, 1997;L'Herminé et al, 2003]. Genetic testing in three other cases was performed because of various combinations of fetal abnormalities found on ultrasound examination (short femur, reduced AC, abnormal posturing of hands, hypogonadism, reduced fetal movements, polyhydramnios, breech presentation and mild hydronephrosis) [Le Bris-Quillevere et al, 1990;Bigi et al, 2008]. In our cohort, 23 amniocenteses were performed and all fetuses had a normal karyotype using Giemsa staining.…”
Section: Discussionmentioning
confidence: 91%
“…Published reports on prenatal diagnosis of PWS are limited to nine cases [Le Bris-Quillevere et al, 1990;Surh et al, 1994;Christian et al, 1996;Roberts et al, 1997;Slater et al, 1997;L'Herminé et al, 2003;Bigi et al, 2008] and a few retrospective reports on prenatal characteristics of children born with PWS [Horsthemke et al, 1996Hiroi et al, 2000Fong and De, 2003;Dudley and Muscatelli, 2007;Whittington et al, 2008;Haugen et al, 2009;Chang et al, 2014;. Recently Geysenbergh et al reported prenatal data of 11 children who were diagnosed postnatally to have PWS, and concluded that the combination of severe growth restriction and polyhydramnios should alert the clinician to perform an invasive test for PWS diagnosis [Geysenbergh et al, 2011].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They claimed that a particular position of hands and feet combined with diminished fetal movements and polyhydramnios is suggestive of PWS. 18 However, fetus C did not present this kind of malposition of the extremities. Dudley and Muscatelli 19 described a genotypedependent variation in the obstetric characteristics of PWS, i.e., deletion or maternal uniparental disomy, making the fetal phenotype difficult to define.…”
Section: Discussionmentioning
confidence: 99%
“…Both subtelomeric MLPA and MRS-MLPA detected a 15q11q13 microdeletion associated with polyhydramnios and hypotonia. Recently, Bigi et al 18 published the first report to describe a possible fetal phenotype in PWS, which could be recognizable after 30 weeks of gestation. They claimed that a particular position of hands and feet combined with diminished fetal movements and polyhydramnios is suggestive of PWS.…”
Section: Discussionmentioning
confidence: 99%